Dissemination of Healthy Lifestyles to Improve HR Quality and Performance at Bina Cipta High School - Bangkit Seandi Taroreh; CH Desi Kusmindari; Poppy Indriani; Rolia Wahasusmiah; Darwin (Jurnal Pengabdian Pancasila (JPP), 2022)
The purpose of community service activities is to increase knowledge about healthy lifestyles to improve the quality of human resources and performance at Bina Cipta High School. The method used is through socialization which consists of three stages, namely planning, implementation and evaluation. Data collection techniques through questionnaires with quantitative data analysis. Socialization was given to 32 people consisting of 30 students and 2 teachers. The result of this activity is an 87% increase in knowledge about healthy lifestyles to improve the quality of human resources and performance, including: 1) the importance of a healthy lifestyle to support sports achievements and scholarship opportunities, 2) the application of ergonomics in the office, 3) improving the quality of human resources in the era of 5.0, 4) implementation of a sharia-based economy, 5) promotion towards integrated Islamic schools.